2023
DOI: 10.1038/s41598-023-27845-4
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and functional impairment affects undergraduate psychology students’ learning in remote emergency teaching during the COVID-19 pandemic

Abstract: This study aimed to explore the impact of anxiety and functional impairment measures on a sample of undergraduate psychology students. Learning performance was evaluated during the emergency remote teaching during the first wave and in the post-vaccination period of the COVID-19 pandemic in Brazil. Data modeling revealed that psychometric indicators of severe anxiety and severe functional impairment predicted students with lower learning performance in pairs of pre- and post-test multiple-choice questions. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…There are two views in existing research on the relationship between exercise duration and anxiety and depression, one view is that exercise duration is the only significant predictor of anxiety reduction through exercise (Patin et al, 2023), and that 20-40 minutes and 75 minutes of aerobic exercise improves anxiety and depression (Yan et al, 2022), respectively, however, the other view is opposite (Nugraha et al, 2023), and those who participated in 10 minutes of exercise had higher levels of anxiety compared to the results of the present agree with the latter view that the duration of exercise does not correlate with anxiety and depression in university students, and is largely based on the effect of exercise frequency. Some studies have shown that anxiety and depression improve with regular exercise, but few people currently engage in regular physical activity for a long period (de Sá et al, 2023), and college students after the COVID-19 pandemic, who felt mentally drained by the various campus epidemic prevention and control measures, were more emotionally sensitive and anxious than usual (Gu et al, 2023), and few students were able to engage in a certain amount of physical activity for a long period, and thus, in one-time physical activity, which has a very short-lived, if any, favourable effect (Massey et al, 2023). Another possibility is the effect of stress on physical activity and exercise, i.e., the experience of stress affects physical activity effort, and college students in the wake of the COVID-19 pandemic face stress in many ways, and thus the favourable effects of exercise may be attenuated or lost.…”
Section: Discussionmentioning
confidence: 99%
“…There are two views in existing research on the relationship between exercise duration and anxiety and depression, one view is that exercise duration is the only significant predictor of anxiety reduction through exercise (Patin et al, 2023), and that 20-40 minutes and 75 minutes of aerobic exercise improves anxiety and depression (Yan et al, 2022), respectively, however, the other view is opposite (Nugraha et al, 2023), and those who participated in 10 minutes of exercise had higher levels of anxiety compared to the results of the present agree with the latter view that the duration of exercise does not correlate with anxiety and depression in university students, and is largely based on the effect of exercise frequency. Some studies have shown that anxiety and depression improve with regular exercise, but few people currently engage in regular physical activity for a long period (de Sá et al, 2023), and college students after the COVID-19 pandemic, who felt mentally drained by the various campus epidemic prevention and control measures, were more emotionally sensitive and anxious than usual (Gu et al, 2023), and few students were able to engage in a certain amount of physical activity for a long period, and thus, in one-time physical activity, which has a very short-lived, if any, favourable effect (Massey et al, 2023). Another possibility is the effect of stress on physical activity and exercise, i.e., the experience of stress affects physical activity effort, and college students in the wake of the COVID-19 pandemic face stress in many ways, and thus the favourable effects of exercise may be attenuated or lost.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, é identificada uma associação entre a maior participação nas atividades e os resultados da aprendizagem dos aprendentes(San Cristóbal et al, 2017). Outra relação encontrada é entre a percepção mais positiva dos indivíduos quanto às metodologias ativas utilizadas e melhores resultados de envolvimento e aprendizagem(Cole, Lennon & Weber, 2019;Romero; Buzón-García & Touron, 2019;Godoy et al, 2021;de Sá et al, 2023).A adoção de estratégias e metodologias de ensino-aprendizagem adequadas ao público-alvo, portanto, é essencial. O educador, ao fomentar o desenvolvimento de uma visão crítica do aprendente em relação ao conteúdo a que é exposto permite o confronto entre conhecimento e realidade em que esse estudante se insere, possibilitando o envolvimento do aprendiz com seu processo de aquisição de conhecimento.…”
unclassified